2015
DOI: 10.1021/ed500377m
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration and Near-Peer Mentoring as a Platform for Sustainable Science Education Outreach

Abstract: Decreased funding for middle and high school education has resulted in reduced classroom time, which, when coupled with an increased focus on standardized testing, has decreased the exposure of many middle school students to hands-on science education. To help address these challenges, we developed an integrated outreach program, spanning grades 6−12, designed to engage students by bringing students to the University of Oregon to perform hands-on laboratory experiments. Initially developed to supplement scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 22 publications
0
47
0
Order By: Relevance
“…Another popular and effective approach to STEM mentoring is to utilize same‐age or near‐age peer mentors 110–112 . Peer mentors are in a unique position as credible messengers to share their recent experiences with their mentees in pursuing a STEM interest or educational pathway 113 .…”
Section: Resultsmentioning
confidence: 99%
“…Another popular and effective approach to STEM mentoring is to utilize same‐age or near‐age peer mentors 110–112 . Peer mentors are in a unique position as credible messengers to share their recent experiences with their mentees in pursuing a STEM interest or educational pathway 113 .…”
Section: Resultsmentioning
confidence: 99%
“…The near-peer mentoring approach showed a promising impact with 88% of students giving positive feedback on the credibility of the mentors. This approach has been identified as guiding students to a visible education pathway as well as envisioning themselves as future scientists (Pluth et al, 2015). The smaller gender gap between the students and mentors could break the wall and allow a safe space for students to interact and learn science without being labelled or judged.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in science education outreach have shown that mentorship is particularly effective when it occurs between a mentor who has recently passed through the stage of training where the mentee currently resides, as it allows mentees to see themselves in the position of the mentor. 11 Our program presents a unique opportunity to facilitate this relationship between medical students and high school students as they approach their post-secondary schooling. Based on these observations and findings, we hope to grow a codified mentorship component within the program for future years by creating mentor-mentee groups/pairings and organizing mentorship events, such as open office hours and medical student panels.…”
Section: Discussionmentioning
confidence: 99%